STARTUP MARKETING STRATEGY TO ATTRACT VENTURE CAPITAL AT THE AGE OF DIGITALIZATION - Olena Kanishchenko; Yuliia Kuznetsova (Economics & Education, 2020)
The article deals with the current state of startup ecosystem, its constraints and incentives, comparisons with traditional business models. The authors pay attention to an issue of attracting venture capital to finance newborn projects in the modern world. The key problems of the startups are outlined in the paper, an important fact that the ecosystem is getting more competitive and the investors are getting more cautious. The paper summarizes the traditional marketing tools for strategy development and justifies the possibility of their use in building up a startup business model. The features of attracting venture investments are identified and the specifics of the venture investor-consumer are determined. The authors' approach to the creation of a venture capital investment strategy is proposed, and each stage is considered with appropriate management concepts and models. The choice of the most effective instrument for analyzing the macromarketing, micromarketing environment and internal environment of startup obviously depends on market location and type, industry, size of the company, resources, market type, life cycle of the market / product, etc. Many tools for marketing analysis in the modern theory and practice of marketing have been named with the aim to popularize. The paper also considers the influence of coronavirus epidemy of to attract money and figures out some basic information how to prevent such a situation. The key future threats of the market are named. The importance of marketing research in the age of digitization has been explained and proven.